Language and transcendence (Revista de Ciências Sociais, 2020)
Shortly following líghtbreak on August 2, 1986 8the advanced seminar cadets of the Skinner Behavior Contrai Institute began to file into the newly erected geodesic cell. Here in the Neurobiological Division today was to bring their last lecturc on protoplastic diagnosis. All students were presentChief Skinner was to personally present this lecture. Following his customary and general comments on the Students Beta-wave progress indicators, Chief Skinner expressed his grave concern with growing student dissatisfaction related to protoplastic diagnosis and its techno-application to mass behavior charneling.